Twin to Twin Transfusion Syndrome (TTTS): An Interesting Entity in Twin Pregnancy - Srinivas Prasad RH; BV Balakrishna; Ankur Aneja; Vikram N R; Kudva N (JCDR Research and Publications Pvt. Ltd., 2015)
Twin-Twin transfusion syndrome (TTTS) is a condition with high rates of perinatal morbidity and mortality due to its poorly understood etiology and difficulty in diagnosis and treatment. Early diagnosis during antenatal ultrasound is very important in reducing the morbidity and mortality rates. TTTS is a phenomenon exclusive to monochorionic twin pregnancies. The donor twin is characterized by oligohydramnios or anhydramnios, growth restriction and abnormal umbilical artery by Doppler velocimetry. The recipient, on the other hand, is characterized by polyhydramnios, abnormal venous dopplers, cardiac enlargement /failure, and eventually hydrops. Sonologists while evaluating the monochorionic twin should have high index of suspicion for TTTS. The present study reports a classical case of TTTS which was detected accurately by ultrasound and managed efficiently resulting in birth of healthy twins.